2020
DOI: 10.1177/0018720820952907
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wave Motion Intensities on Performance in a Simulated Search and Rescue Task and the Concurrent Demands of Maintaining Balance

Abstract: Objective The purpose of this study was to examine how intensity of wave motions affects the performance of a simulated maritime search and rescue (SAR) task. Background Maritime SAR is a critical maritime occupation; however, the effect of wave motion intensity on worker performance is unknown. Methods Twenty-four participants (12 male, 12 female) performed a simulated search and rescue task on a six-degree-of-freedom motion platform in two conditions that differed in motion intensity (low and high). Task per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…However, especially during bad weather, the conditions at sea itself will probably influence BLS performance as well. This is supported by a recent study by Duncan et al that demonstrated the negative effects of simulated wave motions on search and rescue tasks and maintaining balance (28). Although BLS performance was not tested in their study, rough seas might also affect BLS performance.…”
Section: Discussionsupporting
confidence: 62%
“…However, especially during bad weather, the conditions at sea itself will probably influence BLS performance as well. This is supported by a recent study by Duncan et al that demonstrated the negative effects of simulated wave motions on search and rescue tasks and maintaining balance (28). Although BLS performance was not tested in their study, rough seas might also affect BLS performance.…”
Section: Discussionsupporting
confidence: 62%
“…A decline in human performance as motion perturbations increase is well documented in the literature, but results vary by the task. Studies have shown comparable results in a variety of tasks ranging from seated, micro motor tasks (Malone, 1977) to standing, manual material handling tasks (Duncan et al, 2012; McCleod et al, 1980), to cognitive tasks such as visual search (Duncan et al, 2020). These studies reflect a between-task variability in both task performance and MII occurrence within motion profiles.…”
Section: Discussionmentioning
confidence: 99%